An epidemiological study of computer related health problems and stress among bank employees in the vicinity of a tertiary care hospital - Chavhan, Swati S.; Gokhe, Seema S. Bansode (International Journal Of Community Medicine And Public Health, 2020)
Background: Due to the upsurge in information technology and daily increase in the number of computer usage in banking sector and increasing use of online banking services in India, there is need for research into computer related health problems. The objectives of the study were to estimate prevalence of computer related health problems and stress among Bank employees and to study its association with their working environmental conditions. Methods: A cross sectional study was conducted, with a pre-tested, pre-designed questionnaire in 19 banks among 255 bank employees aged 25 to 50 years by census enumeration method in urban field practice area for 18 months. Inclusion criteria included employees working in current job since the past 2 years and on computer for at least 5 days/week and minimum 4 hours/day. The questionnaire included socio-demographic details, working environment and problems experienced while working on computers. Modified standardized Nordic questionnaire (musculoskeletal), depression anxiety stress scales (DASS) (stress), Snellen`s-Jaeger’s chart (visual acuity) and digital lux meter (illumination) was used. Statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 25.0. Results: The proportion of musculoskeletal, symptoms of Carpal tunnel syndrome due to keyboard use, visual problems and stress was found to be 69%, 60%, 58% and 38% respectively. Statistically significant association was found between visual, musculoskeletal complaints and duration of service, time spent on computers, level of computer desktop and ergonomic design of sitting chair. Stress had significant co-relation with age, duration of service, duration of using computers and addictions. Conclusions: Banks should adopt ergonomic workplace design for better health, well-being and productivity of bank employees.